2020
DOI: 10.1177/1024907920971159
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary resuscitation training in secondary education: A prospective cross-sectional survey of 110 Hong Kong secondary schools

Abstract: Background: Hong Kong rates of bystander cardiopulmonary resuscitation are very low by international standards. Several Hong Kong secondary schools have begun incorporating cardiopulmonary resuscitation training into their curriculums for teachers and students. Objective: This study aimed to explore secondary school cardiopulmonary resuscitation programs and better understand school principals’ attitudes toward cardiopulmonary resuscitation training. Methods: A cross-sectional survey was sent to all Hong Kong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Moreover, there were fewer cardiac arrests in public places during the pandemic, which may have influenced the survival rate of patients with OHCA. Additionally, the lack of sufficient CPR training in HK [ 30 , 31 ] and the fear of COVID-19 may have affected the willingness of witnesses to perform CPR. Given that CPR is considered an aerosol-generating procedure with a significant risk of viral transmission, witnesses may have hesitated to perform it, potentially affecting the STA rate [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there were fewer cardiac arrests in public places during the pandemic, which may have influenced the survival rate of patients with OHCA. Additionally, the lack of sufficient CPR training in HK [ 30 , 31 ] and the fear of COVID-19 may have affected the willingness of witnesses to perform CPR. Given that CPR is considered an aerosol-generating procedure with a significant risk of viral transmission, witnesses may have hesitated to perform it, potentially affecting the STA rate [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is somewhat consistent with the recent literature. 9,11,20,22 Many studies documented a positive association with teachers' willingness levels 10,20,23,24 and only one study found a link between perceived control behaviour and CPR implementation in school. 9 As for CPR training barriers, legal liability seems to be a worldwide concern.…”
Section: Discussionmentioning
confidence: 99%
“… 7 School principals on the other hand addressed; course time restriction, finding a trainer, inadequate funding and support, students and parents disapproval are perceived difficulties in implementing CPR training in their schools. 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation